PENGEMBANGAN E-MODUL BERBANTUAN LIVEWORKSHEETS PADA MATERI FLUIDA STATIS UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Yusuf, Yusniati H. Muh.; Hali, Antonius Suban; Febriani Jessyca Melithah Nuba (Charm Sains: Jurnal Pendidikan Fisika, 2025)
In the learning process, teachers need to provide learning resources that can increase students' interest in learning. The learning resources that are widely used today are textbooks provided at school and also e-books given by teachers to students for independent learning at home. However, textbooks and e-books have exactly the same appearance and are static, giving the impression of being less attractive. The purpose of this study was to produce an e-module assisted by liveworksheets that is valid and effective in increasing the interest in learning of class XI students of SMA Negeri 3 Kupang. The development model used in this study is the ADDIE model (design, development, implementation, evaluation). At the analysis stage, it was found that students need learning resources that can increase interest in learning, so at the development stage the researcher developed an e-module assisted by liveworksheets while simultaneously conducting a validity test. Furthermore, at the implementation stage, an effectiveness test was carried out by class XI students of SMA Negeri 3 Kupang. This states that the e-module assisted by liveworksheets is valid and effective in increasing students' interest in learning.